An empirical model for predicting hydraulic conductivity of mine tailings - Adajar, Mary Ann Q. (Animo Repository, 2014)
To evaluate the applicability of mine tailings as embankment materials, its geotechnical characteristics have to be established. Standard ASTM procedures are performed to determine the physical properties and hydraulic conductivity of mine tailings from three (3) different mining sites in the Philippines. Falling head permeability tests are performed on reconstituted samples compacted at varying void ratio and fine content. The hydraulic conductivity, k of tailings falls within the range of 10-3 to 10-6 cm/sec. Data obtained from these tests are used to develop an empirical model for predicting the hydraulic conductivity of mine tailings under fully saturated conditions as a function of void ratio and fine contents. The formulated model is a useful tool to estimate the hydraulic conductivity of non-plastic fine tailings, a parameter needed in seepage analysis, when these waste materials are used as embankment materials in the construction of tailing dams. © 2014, International Journal of GEOMATE.